Exploring Academic Paradise: Faculty Job Satisfaction in the Business Program at Shanker Dev Campus - Karki, Puspa; Tamang, Sabu; Khadka, Purnika; Khadka, Ritika; Budhathoki, Sabin; Parajuli, Suman Kamal (International Journal of Atharva, 2024)
The purpose of this research is to examine the level of satisfaction felt by business program faculty at Shanker Dev Campus (SDC). The research aims to evaluate several hypotheses about demographic parameters including gender, age, and work experience on faculty satisfaction levels. A total of 35 randomly selected faculty members were asked to fill out a standardized questionnaire. A low standard deviation of 0.55682 indicates consistency across respondents, and a mean satisfaction score of 3.9871 indicates that faculty members are typically satisfied with job. A Pearson correlation coefficient seems to indicate no statistical significance when examining the relationship between age, job satisfaction, and work experience. As far as gender disparities in work satisfaction depart, female respondents were somewhat more satisfied on average than male respondents. These findings provide valuable insights into the dynamics among SDC's business program faculty and can help shape initiatives that increase faculty satisfaction and program achievement.